Resensi Buku:: Writing/Reading the Bible in Postcolonial Perspective - Salomo Sihombing (TRANSFORMATIO: Jurnal Teologi, Pendidikan, dan Misi Integral, 2024)
The book Writing/Reading the Bible in Postcolonial Perspective, hereinafter referred to as "this book," provides a powerful revolution in biblical studies. This book was written by Steed Vernyl Davidson who is Associate Professor of Hebrew Bible/Old Testament at McCormick Theological Seminary, Chicago IL. He served as dean of the faculty and vice chancellor for academic affairs. Davidson focuses on the critical interpretation of biblical texts, his work emphasizing inquiry into the reading of texts through critical lenses such as postcolonial studies, gender and feminist studies, critical-geography, and critical-race theory.